“Water is the Oldest of Ointments”: In Search of Historical Meanings and Contexts of Use - Kallio, Kati (Elore, 2024)
The proverb "Water is the oldest of ointments" is widely used in contemporary Finnish society, referring to clean or potable water, hygiene, and the overall importance of water. In this article, I give an example of how diverse and ambiguous the historical field of use and meaning of just one short proverb can be. At the same time, I discuss the methodological possibilities and problems of computationally assisted reading of historical oral poetry. In historical oral tradition in Karelia, Ingria, and Finland, the idea “water is the oldest” was crystallised as clusters of alternating parallel verses and motifs. The most common form of the central phrase is “Water is the oldest of brothers”, used especially in healing charms associated with iron, fire, wood or snakes. The verse “Water is the eldest of ointments” was less common, occurring especially in the context of healing in the sauna and by bathing, of making ointments, and in fire charms. In historical oral poetry, the proverb opens into a vast network of images and motifs, in which water is the oldest and is recurrently linked to the mythological being Väinämöinen, the oldest of sages. In Finnic oral poetry, old age equals knowledge, and knowledge, in turn, equals strength, i.e. with the ability to influence, control or negotiate. The contemporary proverbial use of only one phrase is in continuity with the complex oral uses that preceded it but creates new associations. Many of the earlier layers of meaning – such as the idea of the power of old age, or of healing by charms, sauna and bathing – have been left behind, although, for example the connection with the sauna as a place of cleaning and purification, remains. Tulkintoja historiallisesta kansanperinteestä käytetään yhteiskunnassa laajasti. Laajoja kansanperinneaineistoja kattavat tutkimukset on kuitenkin tehty pääosin jo 1900-luvun alkupuolella oman aikansa tulkintakehysten puitteissa. Tämän tutkimuksen kriittiselle arvioinnille, lähteiden uudelleenluennoille ja tutkimustiedon popularisoinnille on ...